Degenerated benign pelvic neurilemmoma. Case report - Pérez-Ortiz, Viorkis (2019)
Neurilemmomas are rare benign tumors derived from the peripheral nerve sheath and composed of perineural Schwann cells proliferating in a characteristic pattern. They are usually benign, slow-growing and often detected incidentally or by local symptoms secondary to compression of neighboring organs. These solitary tumors are located mainly in head and neck, frequently along the path of peripheral nerves, and are particularly rare as retroperitoneal and pelvic tumors. They represent less than 1% of pelvic tumors, and can reach large dimensions. Degenerated or ancient neurilemmomas present typical degenerative characteristics secondary to aging and decreased vascularization. These characteristics can lead to misinterpretation and confusion with a malignant lesion. Tumors are well encapsulated and recurrences are rare following complete surgical excision. The potential risk of surgical excision is neurological injury. We present the case of a degenerated benign pelvic neurilemmoma.